Pengaruh Kualitas LayananTerhadap Kepuasan Dan Loyalitas Pengguna Elektronik Maal (E-Maal) Perspektif Islam Di Toko Basmalah Di Kabupaten Bondowoso - Muhammad, Nur; Zainur Ridho, Muhammad; Rizqi, Moh; Mardotillah, Mardotillah; Habibatul Awalia, Fita (At-Turost : Journal of Islamic Studies, 2022)
Good service quality will be a motivating factor for consumers to use the E-Maal card product which is part of the Toko Basmalah program. Where in the service there is an element of Shari'ah offered. With good service quality will create satisfied users so that the benchmark of something that is felt and received through various services provided by service providers, which is in accordance with the expectations desired by consumers. Loyalty, conveying positive things and recommending products that are a form of loyalty by consumers/users to E-Maal products. For this reason, the purpose of this study was to determine the effect of service quality on user satisfaction and loyalty from an Islamic perspective at the Basmalah Store in Bondowoso, to determine the effect of service quality on user satisfaction, the effect of service quality on user loyalty and the effect of satisfaction. on user loyalty (E-Maal). The method used in this research is quantitative with an explanatory research approach, with a sample of 110 respondents. While the sampling used incidental sampling. data analysis using path analysis with F test and t test. Hypothesis testing was carried out with the help of the Statistical Package for the (SPSS) software version 24. Service quality had a positive effect on user satisfaction, service quality had a positive effect on user loyalty, and user satisfaction had a positive effect on user loyalty.